Twentieth century - Colton, Joel G. frey50; Time Life Books (Time-Life Books New York, 1968)
Surveys the civilization, politics, economics, culture, leaders and important events and trends in the 20th century world.
West in command -- Lights go out -- Scourge of the depression -- World at war -- Awakening of nations -- New balance of power.
Includes bibliographical references and index
Keywords: History, Modern -- 20th century